Developing English Vocabulary Mastery through English Fairy Tale Videos of the Eleventh Grade Students of SMA Negeri 1 Mamuju - Jumriah Rusdi; Maemuna Muhayyang; Munir Munir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The objective of this study is to assess the progress of students' vocabulary mastery through the use of English fairy tale videos. The quantitative research method was used in this study, with a pre-experimental research design and a sample of 34 students drawn from a cluster random sampling technique. The researchers used the test as an instrument to collect data. Data analysis revealed that by using English fairy tale video media, students' vocabulary mastery improved. The t test value was less than P (0.000 0.05), indicating that hypothesis (H0) of this study was rejected and hypothesis (H1) was accepted. As a result, it is concluded that English fairy tales improve the vocabulary mastery of SMA Negeri 1 Mamuju eleventh grade students.